From Challenge and Response to the Global State: A Reading in the Philosophy of Arnold Toynbee - Al-Zoubi, Amjad Ahmed (Al-Adab Journal, 2019)
Toynbee’s philosophy of civilization was an attempt to draw general lines for the emergence of civilization and its collapse, considering challenge and response as the criterion for this emergence and collapse. Based on this theory, Toynbee deduced his futuristic theory about the global state and the global religion based on common human values. The same questions raised by Toynbee emerge in his work again. The interest in Toynbee’s theory reemerges from last century until know in the context of the communication and civilizational conflict, and the tendency of the world to remove all barriers due to the new technological, political and economic revolutions. The basic premise of this study is that Toynbee extrapolated history and questioned it in the form of a futuristic philosophy in which his experience, work and teaching led him to play a role in this extrapolation. The study covers the following topics:1. The intellectual formation of Toynbee.2. The philosophy of history.3. Challenge, response and the emergence of civilization.4. Collapse of civilization and the global state